Eksistensi Pesantren: Antara Mencetak Ulama dengan Tarikan Modernitas dan Kebutuhan Ekonomis - Haidir; Yuni Shara (CENDEKIA, 2022)
This research actually aims to see the existence of pesantren in the midst of the pull of modernity and the economic needs of the community. Because along with the development of social life which with the progress of the times and the economic needs of the community will change course. We know that at first, pesantren were used as printers for ulama, but now we see not only that and now they have developed into officials, technocrats, businessmen, and others. Therefore, this research was conducted using a qualitative descriptive analysis with a phenomenological approach. Researchers will see firsthand the phenomena that occur in Islamic boarding schools in Medan City. And based on the results of the study it was found: a) The existence of pesantren is the most important thing in the midst of modern human life, therefore people who are economically capable feel proud of their children studying in pesantren, b) They are proud to study in pesantren because the learning system is modern and can continue their education to higher education. General PT, c) The willingness of parents to send their children to Islamic boarding schools because from an economic point of view it is more profitable, for example, in pesantren, the budget is clear, while if their children are sent to public schools, the financing can be greater, because children are freer to use their money.